Pemanfaatan Whatsapp dalam Kuliah Daring di IAIN Salatiga pada Masa Pandemi Covid-19 - Syaefudin Achmad (FONDATIA, 2022)
The COVID-19 pandemic has also had a serious impact on the world of education. Learning at school or lectures on campus which has been carried out face-to-face has turned into online learning or lectures using various applications. One campus that uses various applications for online lectures is IAIN Salatiga. This article aims to examine how to use WhatsApp as a medium in online lectures at IAIN Salatiga. The COVID-19 pandemic has had an impact on the world of education where learning must be done online. WhatsApp is one of the applications that can be used to carry out online learning. The research method used is descriptive qualitative with a participatory action research (PAR) approach. Data collection techniques using observation and interviews. Data analysis techniques using data presentation techniques, data reduction, and drawing conclusions. The results of the study show that WhatsApp can be used for learning media in online lectures which is effective if it uses the right steps, especially for theoretical courses.